Public engagement with Holocaust memory sites in Poland - Popescu, Diana I., 1983- 1983- Herausgeber (The Holocaust and its contexts, 2024)
This book aims to address a neglected field of research by providing evidence-based insights into how contemporary visitors of different national and generational background, especially those of Polish and Jewish descent, experience and reflect on their visits, or on living in the proximity of different sites of memory across Poland, including former concentration and death camps, ghetto sites, and other physical sites such as museums with a connection to the Holocaust